Onomasticon of the Hittite pantheon. - Gessel, B. H. L. van (Handbook of Oriental Studies. Section 1 The Near and Middle East, 1997)
To find your way in the vast Hittite Pantheon is by no means an easy task. In his Onomasticon of the Hittite Pantheon Ben van Gessel lists all Hittite gods as known from primary sources. Their names are listed as written in Hittite, Sumerian and Akkadian. Moreover, deities not mentioned by a proper name are given. The work ends with the unclassifiable fragments of names. Apart from answering questions about the (often confusing) orthography of the gods' names, each entry categorizes information on their epithets, shrines, priests and servants, cult places, attributes and feasts, as well as about the actual locations in the texts . Where necessary, the author refers to relevant literature.